2023
DOI: 10.1097/prs.0000000000010600
|View full text |Cite
|
Sign up to set email alerts
|

Textured versus Smooth Tissue Expanders: a Comparison of Complications in 3,526 Breast Reconstructions

Abstract: Background: Increased understanding of breast implant–associated anaplastic large-cell lymphoma has led to a shift away from textured breast devices. A few small studies have compared the complication rates of textured and smooth tissue expanders (TEs). The aim of this study was to compare complication profiles in patients undergoing two-stage postmastectomy breast reconstruction with either textured or smooth TEs. Methods: The authors performed a retrospective review of female patients who underwent immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Smooth expanders were slightly larger (436 vs 406 mL, P < 0.001) and had higher initial fill volumes (215 vs 182 mL, P < 0.001). Prepectoral placement (32.8% vs 18.9%, P < 0.001) and acellular dermal matrix (46.2% vs 28.4%, P < 0.001) were used more frequently in the more recent group who received smooth expanders 5 …”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Smooth expanders were slightly larger (436 vs 406 mL, P < 0.001) and had higher initial fill volumes (215 vs 182 mL, P < 0.001). Prepectoral placement (32.8% vs 18.9%, P < 0.001) and acellular dermal matrix (46.2% vs 28.4%, P < 0.001) were used more frequently in the more recent group who received smooth expanders 5 …”
mentioning
confidence: 99%
“…The authors selected 5 studies for inclusion in their meta-analysis. Four studies contained explantation data 2–5 . One of these studies, by Nelson et al, 5 reported a large experience at Memorial Sloan Kettering Cancer Center.…”
mentioning
confidence: 99%
See 3 more Smart Citations